Partisipasi Masyarakat Menangani Konflik Manusia dan Hewan Buas (Studi Respon dan Peran terhadap Kebijakan Pemerintah pada Kecamatan Suoh Kabupaten Lampung Barat) - Aliyando Rifansyah; Gesit Yudha; Abd. Qohar (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This research aims to analize the responses of the community, the role of the community, and government policies in handling human-wildlife conflicts in Kalibata Village and Sumber Agung Village, Suoh District, West Lampung Regency. This research explains the conflict by presenting data on conflicts that occurred in 2024. This type of research includes field research, which is research conducted directly within the community with the aim of uncovering information and conducting analysis to obtain a deep understanding of a specific activity or object. The research method used in this study is descriptive qualitative research, utilizing data collection techniques including observation, interviews, and documentation. The research results show that (1) the response from the community reveals differing perspectives among the residents. Some citizens feel that the policy has not been effective because conflicts are still ongoing. Meanwhile, others, including the government and some citizens, believe that the policy has been effective in terms of socialization and prevention, (2) the role of the community in active participation is very important and has a significant impact on determining the success of conflict management, (3) the policies of the West Lampung Regency Government have implemented measures to reduce conflicts. These policies include the formation of task forces, joint patrols, the installation of signs, and appeals for the community to avoid activities alone in hazardous areas and to limit the time spent in gardens.